«Խաչելության» պատկերագրության որոշ առանձնահատկություններ - Կարեն Մնացականյան (ՀՀ ԳԱԱ հրատ.)
Crucifixion as the most cruel means invented by man has a long history. The criminals were cracified on the cross still by Babylon people,by Persian and Phoenix people. In the first years of Christianity the cross was considered as the symbol of cruelty and barbarity. For a long time in the perception of the Christian, cross was the symbol of suffering and monstrous death. It was difficult for them to accept the cross as a symbol o f salvation and beginning of new life, as in daily reality it was the symbol of suffering and death. In the first centuries of the acceptanc o f Christianity, the crucifixion of the Saviour was described superficial and reviewed, especially with the help of the figures of The Old Testament. The idol of crucified Jesus was born in the fifth century in the Middle East countries. Here Jesus was depicted naked,only his sinks were linked with a piece of cloth. The church pursued a purpose ,so to represent the scene o f crucifixion, so that it would turn into hope and win from mourning, symbolizing the new era of humanity history. No more tortured Jesus was described on the cross, but overtoped the Son of God.the World’s Saviour. There are certain kind of crosses but seven-eight sided crosses are more common, we can rarely meet three-sided crosses. On the board that was provided for head was written «ІСХС». In parallet we meet this following writing «IXRN» in Byzantine monuments. Thus we can divide the graphic types of crucifixion in three main groups,as European,Byzantine and Eastern ' Armenian.
Keywords: Fine Arts